(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Becausethe field of literary analysis of fiction, drama, and poetry has a longhistory, many theories exist on how to evaluate and teach literature. Six frequently discussed approaches toliterary analysis include: (1) New Criticism, (2) Structuralism, (3)Stylistics,(4) Reader-Response, (5) Language-Based, and (6) Critical Literacy.The sections that follow will briefly introduce these six approaches anddiscuss the benefits and drawbacks they offer for teaching literature in theEFL classroom.